PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE, GROWTH, DAN FIRM SIZE TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN MANUFAKTURDI BURSA EFEK INDONESIA - Herlian Rizki Widyatama; Totok Dewayanto (Diponegoro Journal of Accounting, 2023)
Company can provide dividends that are large enough so that it will generate interest in the holders of investors to want to invest in the company. Investors prefer companies that can pay large dividends to companies that pay small dividends, andthere are even a few companies that don't pay dividends at all. This dividend distribution policyis affected by Profitability or Return On Assets (ROA), debt policy, free cash flow, and company growth. Factors that influence the provision of dividends at this writing are return on assets (profitability), current ratio (liquidity),debt to equity ratio (leverage), growth (growth), and company size (firm size). Purpose of this study was to test empirically whether profitability, current ratio, leverage, growth, firm size affect dividend policy in manufacturing companies on the Indonesia Stock Exchange partially or simultaneously (together). Population that was used as the object of observation was 110 manufacturing companies on the Indonesia Stock Exchange in the 2016-2020 period.